2021
DOI: 10.1021/acs.jctc.0c01080
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Nucleation and Solid–Solid-Phase Transitions in Triblock Janus Assemblies

Abstract: A model, including the chemical details of core nanoparticles as well as explicit surface charges and hydrophobic patches, of triblock Janus particles is employed to simulate nucleation and solid–solid phase transitions in two-dimensional layers. An explicit solvent and a substrate are included in the model, and hydrodynamic and many-body interactions were taken into account within many-body dissipative particle dynamics simulation. In order not to impose a mechanism a priori, we performed free (unbiased) simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 67 publications
16
44
0
Order By: Relevance
“…It is reported that decreased coating weight generates higher hydrophobicity and surface roughness while thick layers come with fewer empty spaces between the layers, resulting in a reduced hydrophobic effect. In addition, thin layers of filament are most likely to retain the intrinsic unevenness of the surface [34,35]. From Table 5, the predictions of the finite element method were found to be close to the experimental results in some simulations but diverged in others.…”
Section: Simulations and Experimental Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…It is reported that decreased coating weight generates higher hydrophobicity and surface roughness while thick layers come with fewer empty spaces between the layers, resulting in a reduced hydrophobic effect. In addition, thin layers of filament are most likely to retain the intrinsic unevenness of the surface [34,35]. From Table 5, the predictions of the finite element method were found to be close to the experimental results in some simulations but diverged in others.…”
Section: Simulations and Experimental Resultsmentioning
confidence: 65%
“…It is reported that decreased coating weight generates higher hydrophobicity and surface roughness while thick layers come with fewer empty spaces between the layers, resulting in a reduced hydrophobic effect. In addition, thin layers of filament are most likely to retain the intrinsic unevenness of the surface [34,35]. Some studies reported on the extensive hydrophobic nature of thin coating related to the higher roughness [36], while other studies [37] suggested decreased surface roughness as well as hydrophobicity due to filled up voids and formation of large aggregate in the case of multiple layers.…”
Section: Simulations and Experimental Resultsmentioning
confidence: 99%
“…As illustrated by the previous studies, the exact equilibrium location of phase boundaries in the phase separation can be precisely determined by adding a bias to the potential energy of the system to sample different configurations or choosing larger repulsion parameters for the different types of beads to lower the free energy barrier. [ 43 , 44 ] In this work, we mainly focus on the interfacial thermodynamic properties, and it should be noted that the phase transition points (such as the temperature, pressure, and copolymer concentration) are not the exact equilibrium transition conditionist. To save the computational cost and speed up the formation of the interfaces, the PEO, PPO homopolymers, and PEO-PPO-PEO triblock copolymers were initially placed in distinct locations along the x-direction in the box, which can greatly enhance computing efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to the E g of PDTSDTTAZ, PDTSTAZ and PDTSNTDO (1.81, 1.78 and 1.65 eV, respectively), both polymers had a significantly lower E g . The significant lowering of band gaps is thought to be a result of adopting a 2D (thin film) structure since the band gap is known to be low in symmetric 2D soft matter systems [50]. As a result, this new type of polymer adopted more planar structures with a greater intrachain charge transfer alongside the polymer backbone.…”
Section: Molecular Weights and Yield Of The Polymersmentioning
confidence: 99%